2011
DOI: 10.2147/rrn.s15539
|View full text |Cite
|
Sign up to set email alerts
|

Traditional open-bay versus single-family room neonatal intensive care unit: a comparison of selected nutrition outcomes

Abstract: Background:In contrast to the traditional open-bay-type design of the neonatal intensive care unit (tNICU), infants in developmentally appropriate NICU (dNICU) are housed in individual rooms with greater control of light and noise. Previous reports have documented positive influence of the dNICU in cardiorespiratory status, physiologic stability, and weight gain of the infants. The objective of this study was to explore selected nutrition outcomes of infants in the dNICU versus tNICU. Method: A prospective coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…Most (n=14) were before-and-after studies and the remainder were contemporaneous studies. 10 12 17 18 21 43–60 Three studies were low quality and only one had a high-quality score. Many of these studies included statistically assessed findings, with most favouring single rooms or showing no difference between accommodation types.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Most (n=14) were before-and-after studies and the remainder were contemporaneous studies. 10 12 17 18 21 43–60 Three studies were low quality and only one had a high-quality score. Many of these studies included statistically assessed findings, with most favouring single rooms or showing no difference between accommodation types.…”
Section: Resultsmentioning
confidence: 98%
“…Overall, only 25 of the studies included reported p values for differences in baseline characteristics between patients admitted to multibed versus single-bed rooms. Of these 25, only 5 reported significant differences in any parameters (p≤0.05): one study reports lower caregiver’s age at the time of patient’s admission, 9 three report lower gestational age of infants admitted to single rooms in neonatal intensive care unit (NICU) 10–12 and one reports a higher proportion of female patients were admitted to single rooms. 13 The latter study however also notes that patients admitted to single rooms were more frail due to multiple comorbidities and functional dependence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations